IMPLEMENTASI MEDIA PEMBELAJARAN YOUTUBE DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS III PADA MATA PELAJARAN IPAS MI ISLAMIYAH ATTANWIR TALUN SUMBERREJO BOJONEGORO - ROBIATUL ADAWIYAH; AYU NAFILATIN; MIFTAHUL JANNAH (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the implementation of YouTube as a learning media to improve the learning interest of third-grade students in the subject of Science and Social Studies (IPAS) at Madrasah Ibtidaiyah (MI). YouTube was chosen as a learning media due to its ability to present material in a visual and interactive way, which can capture students' attention. The method used in this study is a quantitative approach with an experimental design. Data were collected through questionnaires given to students to measure their learning interest before and after the use of YouTube as a media. The results of the study indicate a significant increase in students' learning interest after the implementation of YouTube, as shown by higher questionnaire scores. Therefore, YouTube as a learning media can be considered an effective alternative in enhancing students' learning interest in the subject of IPAS at MI.